Financing Labor - Benmelech, Efraim; Bergman, Nittai; Seru, Amit (Review of Finance, 2021)
Abstract Financial market imperfections can have significant impact on employment decisions of firms. We illustrate the economic importance of this channel by showing that employment decisions are constrained by firms’ financial health and liquidity. Our main analysis uses a collage of three “quasi-experiments” to trace the effects of finance on employment. The results suggest that financial constraints and the availability of credit play an important role in firm-level employment decisions, as well as aggregate unemployment outcomes.